Proptosis is associated with thiol-disulfide in patients with Graves’ ophthalmopathy - Acibucu,Fettah (2022)
ABSTRACT Objective: Graves’ ophthalmopathy (GO) is a vision-threatening finding observed in approximately half of Graves’ disease patients. The pathophysiology of GO is unclear, and one of the suspected factors is oxidative stress. In our study, we compared the relationship between proptosis and SH-SS in patients diagnosed with GO. Materials and methods: In this prospective study, 40 recently diagnosed Graves’ disease patients with proptosis, 40 recently diagnosed Graves’ disease patients without GO and 30 healthy individuals with similar demographic characteristics were included. Serum thiol-disulfide (SH-SS) measurements were performed. Eye examinations were performed by a single ophthalmologist to check for the presence of GO, and proptosis values were recorded with a Hertel exophthalmometer. Results: Total SH values were lower in the group with proptosis than in the other groups (p < 0.05). Total and native SH values were lower in patients without proptosis than in the control group (p < 0.05). Total SH, native SH and SS levels were independently associated with proptosis (p < 0.05). According to this analysis, it was found that increasing SS and decreasing total and native SH levels increased the probability of proptosis by 24.4%, 32.7% and 32.4%, respectively. Conclusion: A decrease in SH, which is a natural antioxidant that protects the body against oxidative stress, and an increase in SS are important signs of oxidative damage. Proptosis and SH-SS are closely related in GO. This may help us detect GO and proptosis in Graves’ patients. It can also assist in developing new options for preventing and treating GO.